STRATEGI PEMBANGUNAN ZONA INTEGRITAS - Cahyono, Dodik Ari; Suardana, IB Raka (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.07.TAHUN.2021, 2021)
Text This study aims to determine the organizational management strategy with all the capabilities and limitations of organizational resources in going beyond the twists and turns, sacrifices, obstacles and challenges in realizing the development of the integrity zone by implementing effective management and empowering potential employees. as human capital. To serve as a reference as a pilot office in realizing good governance. Qualitative methods with triangulation techniques, namely interviews, field observations and document studies, with the research setting at the Office of Supervision and Service of Customs and Excise Type Madya Pabean Ngurah Rai. The data were analyzed against the interviewee's answers with secondary / supporting data obtained and verification of the validity / validity of the data was carried out with no difference between what the researcher reported and what actually happened to the object under study. In this study, it was found the intricacies of organizational efforts in implementing management in the form of work programs / strategies, innovation, empowerment of employees as human capital and the results of developing the integrity zone.